Implementasi Metode AHP-TOPSIS untuk Keputusan Pembelian Kamera di Perusahaan Jasa Fotografi dan Videografi ASSAD - Abilla, Bait; Retno Prasinta, Widya; Listyana Putri, Azkya (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the selection of the optimal camera for the photography and videography service company Assad ID using a combination of the Analytical Hierarchy Process (AHP) method and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). The rapid development of the photography industry makes choosing the right camera a crucial factor in improving the quality of service. The weighting of criteria using AHP is based on the evaluation of photography and videography experts, including technical specifications, functional features, economic aspects, comfort, and supporting services. The TOPSIS method is applied to the ranking of five alternative cameras (Sony A7 III, Canon EOS R6, Nikon Z6 II, Panasonic Lumix S5, and Fujifilm X-T4). The results of the study show that technical specifications and functionality features have the highest weight. Sony A7 III ranked first with a preference value of 0.610, followed by Canon EOS R6 (0.581), Fujifilm X-T4 (0.472), Nikon Z6 II (0.401), and Panasonic Lumix S5 (0.368). This study proves the effectiveness of the AHP-TOPSIS method in making optimal camera purchase decisions and can be a reference for similar companies in determining the investment of photography and videography equipment according to operational needs